2012
DOI: 10.1155/2012/681207
|View full text |Cite
|
Sign up to set email alerts
|

Study Bioprospecting of Medicinal Plant Extracts of the Semiarid Northeast: Contribution to the Control of Oral Microorganisms

Abstract: Dental pathologies can be caused by plaque-forming bacteria and yeast, which reside in the oral cavity. The bacteria growing in dental plaque, a naturally occurring biofilm, display increased resistance to antimicrobial agents. The objective was the evaluation of a preclinical assay of medicinal plants of the semiarid region from the northeast against oral pathogenic microorganism, aiming at bioprospecting a new product. The selection of plant material for this study was based on the ethnobotanical data on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 27 publications
0
28
0
2
Order By: Relevance
“…Although it is not a natural species, atemoia results from the crossing over of two fruits that belong to genus Annona ; therefore, the presence of acetogenins in its seeds is expected as well as other different compound(s) that could be causing a synergic effect together with acetogenins changing the curve's shape. Caramori studied nutritional value and activity of several enzymes and antinitritional factors in some seeds from Brazilian cerrado fruits, including araticum and ( SANTOS et al, 2007SANTOS et al, , 2010LACHUMY et al, 2010;POUR;SASIDHARAN, 2011;SILVA et al, 2012). Moreover, Artemia salina bioassay proved more accurate and sensitive to detect such compounds than the standard method using mice, previously proposed by the Association of Official Analytical Chemists for food biotoxins analysis (ASSOCIATION…, 1990;PARRA et al, 2001;GARCIA-RODRIGUEZ et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Although it is not a natural species, atemoia results from the crossing over of two fruits that belong to genus Annona ; therefore, the presence of acetogenins in its seeds is expected as well as other different compound(s) that could be causing a synergic effect together with acetogenins changing the curve's shape. Caramori studied nutritional value and activity of several enzymes and antinitritional factors in some seeds from Brazilian cerrado fruits, including araticum and ( SANTOS et al, 2007SANTOS et al, , 2010LACHUMY et al, 2010;POUR;SASIDHARAN, 2011;SILVA et al, 2012). Moreover, Artemia salina bioassay proved more accurate and sensitive to detect such compounds than the standard method using mice, previously proposed by the Association of Official Analytical Chemists for food biotoxins analysis (ASSOCIATION…, 1990;PARRA et al, 2001;GARCIA-RODRIGUEZ et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…After the incubation period was added 20 µL of aqueous resazurin solution (Sigma-Aldrich ® ) at 0.01% for visual reading of antimicrobial activity. [19][20][21] The MIC was defined as the lowest concentration of antimicrobial agent, which prevented the visible growth of the microorganism in sensitivity tests, 17 verified through change of the medium color. For determinations of minimum bactericidal concentration (MBC) and minimum fungicidal concentration (MFC), a portion of the well corresponding to MIC and previous wells was shown in agar BHI plus sheep blood (5%) for bacteria, and agar sabouraud dextrose for yeast.…”
Section: Microorganisms and Susceptibility Testingmentioning
confidence: 99%
“…These findings are in line with those of a previous bioprospection study on medicinal plants of the semiarid region of northeastern Brazil. 23 It has been reported that substances showing MIC up to 500 µg/mL are considered strong antimicrobial agents; moderate if between 500 and 1000 µg/mL; and weak if above 1000 µg/mL. 24,25 With a MIC of 15.62 µg/mL against planktonic C. albicans, B. forficata extract was further selected to be tested against C. albicans biofilm adhesion.…”
Section: Discussionmentioning
confidence: 99%